The Paleoecology of Microplastic Contamination - Bancone, Chiara E. P.; Turner, Simon D.; Ivar do Sul, Juliana A.; Rose, Neil L. (Frontiers in Environmental Science, 2020)
While the ubiquity and rising abundance of microplastic contamination is becoming increasingly well known, there is very little empirical data for the scale of their historical inputs to the environment. For many pollutants, where long-term monitoring is absent, palaeoecological approaches (the use of naturally-accumulating archives to assess temporal trends) have been widely applied to determine such historical patterns, but to date this has been undertaken only very rarely for microplastics, despite the enormous potential to identify the scale and extent of inputs as well as rates of change. In this paper, we briefly review the long-term monitoring and palaeoecological microplastic literature before considering the advantages and disadvantages of various natural archives (including lake and marine sediments, ice cores and peat archives) as a means to assess microplastic records, as well as the range of challenges facing those attempting to extract microplastics from them. We also outline some of the major considerations in chemical, physical and biological taphonomic processes for microplastics as these are critical to the correct interpretation of microplastic palaeoecological records but are currently rarely considered. Finally, we assess the usefulness of microplastic palaeoecological records as a stratigraphic tool, both as a means to provide potential chronological information, as well as a possible marker for the proposed Anthropocene Epoch.